'At the heart of human politics': agency and responsibility in the contemporary climate novel. Issue 1 (2nd January 2022) - Cole, Matthew Benjamin
ABSTRACT: How might climate fiction inform public perceptions of climate change and its political stakes? While early proponents of climate fiction called on writers to move the public with visceral cautionary tales, recent climate fiction and criticism thereof aims beyond apocalyptic and catastrophic representation, reflecting broader debates regarding fear and agency in the climate imaginary. This context clarifies the modes of imaginative engagement pursued in recent English-language climate novels, including Kim Stanley Robinson's New York 2140, Richard Powers' The Overstory, and Amitav Ghosh's Gun Island . These works respond to patterns of denial and depoliticization by challenging their audiences to reimagine agency and responsibility in politically expansive and ethically demanding terms. Dramatizing complex interconnections between communities, generations, and species, as well as the obligations and possibilities for action to which they give rise, they enrich the climate imaginary by illuminating political potential amidst the overwhelming crisis.